Linguistic Landscape Analysis of Commercial Space: A Case Study of Tokio 「とこや」 Barber Shop Signage in Bali and Bing Pop Restaurant Signage in Literacy and Learning Perspective - Budi, Imanuel Setyo; Launingtia, I Gusti Ayu Niken; Pramesti, Putu Dewi Merlyna Yuda (Journal of Practice Learning and Educational Development, 2025)
This study analyzes the linguistic landscape in commercial spaces with a case study of two business signs in Indonesia, namely Tokio 「とこや」Barber in Bali and Bing Pop Restaurant in Probolinggo. This study aims to reveal how the use of language and visual elements in signboards reflects identity, marketing strategies, and local socio-cultural dynamics. The method used is qualitative descriptive with a semiotic and sociolinguistic approach, through field observation and visual documentation. The results of the analysis show that the Tokio 「とこや」Barber signboard utilizes Japanese linguistic aesthetics and characters to build an exclusive and modern image, while Bing Pop uses popular language styles and bright colors that reflect a local and friendly approach. Both signboards show a shift in the function of commercial spaces as a place to express global and local linguistic and cultural identities. Furthermore, this study highlights the educational value of the linguistic landscape, as it encourages public literacy in recognizing multilingual expressions, cultural diversity, and the role of visual language in shaping perception. Thus, the linguistic landscape not only represents the language used, but also becomes a visual communication medium that influences public perception of a brand or business space, while fostering broader awareness of language learning and cultural literacy.